CASP4 can be a diagnostic biomarker and correlated with immune infiltrates in gliomas - Tian, Guopeng; Li, Qiao; Niu, Liang; Luo, Yusong; Wang, Hongyu; Kang, Wei; Fang, Xiang; Bai, Shengwei; Yuan, Guoqiang; Pan, Yawen (Frontiers in Oncology, 2023)
Background Gliomas are the most common and invasive malignant tumors that originate in the central nervous system. Currently, the primary treatment modality for gliomas is maximum surgical resection, supplemented by radiotherapy and chemotherapy. However, the long-term survival rate has not signifificantly increased. Pyroptosis is a new form of programmed lytic death that has been recently discovered. Caspase 4 (CASP4) plays a key role in pyroptosis. Many studies have shown that pyroptosis is not only related to inflflammation but is also closely related to the occurrence and development of most tumors. This study aimed to prove that CASP4 has a key role in the mechanism of gliomas. Methods We used expression data from The Cancer Genome Atlas and the Chinese Glioma Genome Atlas to explore the relationship between CASP4 expression and glioma prognosis. The differential expression of CASP4 in gliomas and normal tissues was fifirst tested, and then the connection between CASP4 and tumor prognosis was explored. The relationship between CASP4 expression and immune cell infifiltration was also investigated. Finally, the possible pathways were analyzed using Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and Gene Set Enrichment Analysis. Results CASP4 was highly expressed and associated with a signifificantly lower survival rate in patients with glioma. It could also inflfluence immune cell infifiltration by releasing cytokines. Conclusion CASP4 can be a diagnostic biomarker and is a promising therapeutic target for gliomas.